Rod-like manganese oxide for removing aldehyde, preparation method of rod-like manganese oxide, active manganese tablet and preparation method of active manganese tablet
By using rod-shaped manganese oxide catalysts, the problems of low formaldehyde removal efficiency, light source dependence and high cost in the existing technology are solved, and formaldehyde removal effects that are efficient, economical and non-light dependent are achieved.
Patent Information
- Application Number
- CN202411526208.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-24
AI Technical Summary
The prior art has problems of low efficiency, light source dependence, high cost and by-product threats to health in removing formaldehyde from indoor air.
Using a stick -shaped manganese oxide catalyst, through the reaction of concentrated sulfuric acid, scales graphite, and potassium permanganate, combined with the use of neutralizers to prepare granified graphene with a large amount of manganese hydroxide Mn: o = 1: 2.0-2.2 stick-shaped manganese oxides.
The removal effect of normal temperature catalytic, light -free dependence, high catalytic efficiency, repeated use and low cost removal effect, formaldehyde removal rate can reach 94.3%.
Smart Images

Figure CN119346102A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of formaldehyde catalytic decomposition, and particularly relates to rod-shaped manganese oxide for removing formaldehyde and a preparation method thereof, as well as an active manganese sheet and a preparation method thereof. Background Art
[0002] Formaldehyde is a common organic compound that is widely used in the production process of industries such as construction, furniture, and textiles. However, formaldehyde is extremely harmful to human health. Long-term exposure to formaldehyde may cause irritation of the eyes, nose, and throat, and cause symptoms such as headaches, nausea, and difficulty breathing. What's more serious is that formaldehyde has been listed as a carcinogen by the World Health Organization (WHO) and is closely related to the occurrence of various cancers such as nasopharyngeal carcinoma and leukemia. Therefore, how to effectively remove formaldehyde from indoor air and protect people's health has become an urgent problem to be solved.
[0003] Photocatalytic technology is a method that uses light energy to excite the surface of a catalyst (such as titanium dioxide) to produce strongly oxidizing free radicals, thereby decomposing organic pollutants such as formaldehyde into harmless substances. However, photocatalytic technology has obvious disadvantages in practical applications. First, photocatalytic technology is highly dependent on light sources, especially ultraviolet light sources, which limits its application in indoor environments with insufficient light or at night. Secondly, the efficiency of photocatalytic technology is affected by many factors such as the surface area of the catalyst, light intensity, and pollutant concentration, making it difficult to achieve stable and efficient formaldehyde decomposition. In some high-end photocatalytic systems, precious metals (such as platinum, palladium, etc.) are often used as co-catalysts to improve catalytic efficiency. However, the use of precious metals brings about the problem of high costs. Precious metal resources are limited and expensive, which increases the manufacturing cost and use cost of photocatalytic technology. In addition, precious metal catalysts have poor stability and are easily deactivated by environmental factors, reducing the service life of photocatalytic technology.
[0004] In addition to photocatalyst technology, there are also some methods that use oxidizing substances (such as ozone, hydrogen peroxide, etc.) to remove formaldehyde. However, these oxidizing substances are highly corrosive and can easily damage indoor equipment, furniture, etc. At the same time, these oxidizing substances will produce some by-products in the process of decomposing formaldehyde, such as organic acids, aldehydes, etc. These by-products may pose new threats to human health. In addition, the decomposition effect of oxidizing substances is often not long-lasting, and new oxidants need to be added regularly, which increases the cost of use and the difficulty of operation.
[0005] In order to overcome the drawbacks of the above technologies, researchers have begun to explore methods of introducing active manganese as a catalyst in recent years. Active manganese has high catalytic activity and stability, and can effectively decompose formaldehyde in a wide range of temperature and humidity. Compared with photocatalyst technology and oxidizing substances, active manganese catalysts have high efficiency, durability and cost advantages. The traditional method is to load manganese dioxide in a graphene (or graphene oxide) dispersion, with a small loading amount. At the same time, the production of graphene oxide will produce waste acid, which will pollute the environment. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a rod-shaped manganese oxide for removing formaldehyde, which has the advantages of room temperature catalysis, no light dependence, high catalytic efficiency, reusability and low cost in removing formaldehyde. The present invention also provides a preparation method thereof, and an active manganese sheet for removing formaldehyde prepared by using the rod-shaped manganese oxide and a preparation method thereof.
[0007] The method for preparing the layered manganese oxide for removing formaldehyde of the present invention comprises the following steps: (1) reacting concentrated sulfuric acid, flake graphite and potassium permanganate at 30-85° C. for 1-48 hours to obtain a mixture 1; based on the total mass of concentrated sulfuric acid, flake graphite and potassium permanganate being 100%, the mass fractions of concentrated sulfuric acid, flake graphite and potassium permanganate are 40%-90%, 1%-30% and 1%-30% respectively; the mass fraction of concentrated sulfuric acid is ≥98%; the flake graphite sheet diameter is 40-5000 mesh; (2) adding neutralizer 1 and neutralizer 2 to the mixture in sequence, adjusting the pH value to 5-9, to obtain mixture 2; neutralizer 1 is one or more oxides or hydroxides of rare earth elements; neutralizer 2 is one or more hydroxides of alkali metal elements and oxides or hydroxides of alkaline earth metals; the mass ratio of neutralizer 1 to neutralizer 2 is 1:(0.1-10); In the process of adjusting the pH value, due to the change in viscosity caused by the change in pH, water can be appropriately added for dilution; through the above reaction, graphene oxide loaded with a large amount of manganese hydroxide is obtained; The cations in the neutralizer 1 and the neutralizer 2 and the original manganese ions in the system gradually change from a solution state to cation-doped manganese hydroxide, manganese oxyhydroxide, and manganese dioxide precipitates (manganese oxyhydroxide and manganese dioxide are oxidized by residual potassium permanganate under alkaline conditions). The precipitates exist in large quantities between and on the surface of the intercalated graphene oxide, forming a rod-like structure. (3) After the mixture is aged for 1-48 hours, the supernatant is removed, the precipitate is centrifuged, and then washed to a pH value of 6-8 for a 1wt.% aqueous dispersion, and then dried at 80-200°C to obtain a dried product; during the drying process, as the temperature rises, the graphene oxide pre-expands, further increasing the looseness of the manganese hydroxide or oxide, which is convenient for subsequent tubular furnace oxidation. At the same time, manganous hydroxide is converted into manganese hydroxide, and a small amount is converted into manganese oxide; (4) placing the dried product in a tube furnace and sintering it in a nitrogen-oxygen mixed atmosphere to obtain the rod-shaped manganese oxide. The volume ratio of nitrogen and oxygen is (1-10):1, the sintering temperature is 300-800°C, and the sintering time is 0.5-6h, and the rod-shaped manganese oxide with Mn:O=1:2.0-2.2 and a C content of 3-10% can be obtained.
[0008] In the present invention, when Mn:O>1:2.0, the valence state of Mn ions is less than +4, and tends to be +4. Doped ions are not suitable to combine with O in vacancies and are easily washed away during the washing process. When Mn:O<1:2.2, there are many vacancies, and the intervention of doped ions affects the crystal form of manganese oxide, and it is not easy to achieve a good catalytic effect. Since graphene (graphene oxide) has a large specific surface area, a small amount can form an effective load. When the carbon content is greater than 10%, it is easy to be coated, which reduces the contact between vacancies and harmful gases, oxygen and water vapor in the air, affecting the catalytic oxidation effect; when the carbon content is less than 3%, the active sites provided cannot reach the maximum level, which will also affect the catalytic oxidation reaction.
[0009] The present invention prepares rod-shaped manganese oxides with different Mn:O:C ratios by controlling the sintering temperature and the oxygen content in the nitrogen-oxygen mixed gas, and the rod-shaped manganese oxides have different doping ions according to the different cations in step (2). The higher the reaction temperature and the longer the reaction time, the lower the C content in the graphene oxide. Under the condition that the oxygen content in the mixed gas is not changed, the Mn:O ratio remains basically unchanged; with the increase of the sintering temperature and the oxygen in the nitrogen-oxygen mixed gas, the ratio of O in the manganese oxide compound increases.
[0010] The rod-shaped manganese oxide for removing formaldehyde described in the present invention is prepared by adopting the above preparation method.
[0011] The active manganese sheet for removing formaldehyde prepared by using the rod-shaped manganese oxide described in the present invention is composed of a PET long fiber layer 1, a mixed glue layer 1, a PET short fiber layer, a mixed glue layer 2, and a PET long fiber layer 2 from bottom to top, wherein the PET long fiber layer 1 and the PET long fiber layer 2 are composed of PET long fibers, the PET short fiber layer is composed of ultrafine PET short fibers, the mixed glue layer 1 and the mixed glue layer 2 are composed of manganese oxide mixed glue, and the manganese oxide mixed glue is mixed by mixing the following raw materials by mass fraction: Rod-shaped manganese oxide: 10%-20%, Heavy calcium powder: 10-20%, Modified acrylic emulsion: 10%-20%, Dispersant: 0.3%, Wetting agent: 0.1%, The balance is water.
[0012] Preferably, the ultrafine PET short fibers have a fineness of ≤0.4 dtex and a length of ≤3 mm; the PET long fibers have a fineness of 1.7-2.3 dtex and a length of ≥38 mm.
[0013] The method for preparing the active manganese sheet of the present invention comprises the following steps: (1) Ultrafine PET staple fibers and PET long fibers are opened in an opening machine respectively; (2) Spreading the opened PET long fibers evenly on a polytetrafluoroethylene conveyor belt to form a PET long fiber layer; (3) spraying a layer of manganese oxide mixed glue on the PET long fiber layer 1 to form a mixed glue layer 1, then evenly spreading a layer of ultrafine PET short fiber on the mixed glue layer 1 to form a PET short fiber layer, then spraying a layer of manganese oxide mixed glue on the PET short fiber layer to form a mixed glue layer 2, and finally evenly spreading a layer of PET long fiber on the mixed glue layer 2 to form a long fiber layer 2, to obtain a composite material; (4) Pre-drying the composite material in a microwave oven, passing through a hot roller, and passing through a hot air dryer to obtain a dried composite material; wherein the pre-drying power is 200-500W / m 2 The pre-baking time is 1-3 minutes. The main purpose of pre-baking is to reduce the moisture in the composite material and increase the initial bonding force. The temperature of the overheating roller is 120-160℃, which increases the compactness of the composite material and the uniformity of the distribution of manganese oxide. (5) The dried composite material is shaped by a second hot pressing roller at a temperature of 140-160°C.
[0014] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention can prepare graphene-loaded manganese dioxide material in one step. Compared with the traditional method of loading manganese dioxide in a graphene (graphene oxide) dispersion, the loading fastness of manganese dioxide in the present invention is better and it is not easy to detach after ultrasound. At the same time, the waste acid generated by the production of graphene oxide is directly salted to reduce the generation of waste acid; 2. The doping ions of the present invention are convenient. After the neutralizer is added, the sulfuric acid concentration of the system is high, most of the metal ions are in a free state, and the doping is more uniform; 3. The active manganese tablets obtained by the present invention have better formaldehyde removal effect, lower manganese oxide dosage, and the formaldehyde removal rate can reach 94.3%.
[0015] 4. The upper and lower layers of conventional long fibers of the active manganese sheet of the present invention can provide better dimensional stability and have less effect on air permeability; the ultra-fine PET short fibers have a larger area, can provide more contact surfaces for catalytic oxidation reactions, adsorb more glue, and reduce the coating of glue on the active manganese material; the first hot pressing in the preparation of the active manganese sheet effectively increases the distribution uniformity of the manganese oxide glue mixture; 5. The composite process and material formula of the active manganese flakes of the present invention can prevent the active manganese flakes from falling off after being formed. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is a SEM image of the manganese oxide of Example 1 of the present invention. DETAILED DESCRIPTION
[0017] The technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and embodiments.
[0018] Unless otherwise specified, all raw materials used in the examples are commercially available.
[0019] Example 1 The method for preparing the rod-shaped manganese oxide for removing formaldehyde comprises the following steps: (1) Concentrated sulfuric acid (98% by mass dispersion), flake graphite (flake diameter 325 mesh), and potassium permanganate (based on the total mass of concentrated sulfuric acid, flake graphite, and potassium permanganate being 100%, the mass fractions of concentrated sulfuric acid, flake graphite, and potassium permanganate are 50%, 30%, and 20%, respectively) are reacted at 65° C. for 24 h to obtain a mixture 1.
[0020] (2) Adding cerium oxide and sodium hydroxide to mixture one in sequence, adjusting the pH value to 7.5, to obtain mixture two; the mass ratio of cerium oxide to sodium hydroxide is 1:0.5.
[0021] (3) After the mixture is aged for 48 hours, the supernatant is removed, the precipitate is centrifuged, and then washed to a pH value of 7 for a 1 wt.% aqueous dispersion, and then dried at 120° C. to obtain a dried product; (4) placing the dried product in a tube furnace and sintering it in a nitrogen-oxygen mixed atmosphere to obtain the rod-shaped manganese oxide, wherein the volume ratio of nitrogen and oxygen (mixed gas) is 9:1, the sintering temperature is 550°C, and the sintering time is 3h, to obtain the rod-shaped manganese oxide with a Mn:O ratio of 1:2.1 and a C content of 7%.
[0022] Example 2 The method for preparing the rod-shaped manganese oxide for removing formaldehyde comprises the following steps: (1) Concentrated sulfuric acid (98% by mass dispersion), flake graphite (flake diameter: 325 mesh) and potassium permanganate were reacted at 65°C for 24 h to obtain a mixture (based on the total mass of concentrated sulfuric acid, flake graphite and potassium permanganate being 100%, the mass fractions of concentrated sulfuric acid, flake graphite and potassium permanganate being 50%, 30% and 20% respectively).
[0023] (2) Adding cerium oxide and sodium hydroxide to the mixture in sequence, adjusting the pH value to 7.5, and obtaining a mixture II; wherein the mass ratio of cerium oxide to sodium hydroxide is 1:10.
[0024] (3) After the mixture is aged for 48 hours, the supernatant is removed, the precipitate is centrifuged, and then washed to a pH value of 7 for a 1 wt.% aqueous dispersion, and then dried at 120° C. to obtain a dried product; (4) placing the dried product in a tube furnace and sintering it in a nitrogen-oxygen mixed atmosphere to obtain the rod-shaped manganese oxide, wherein the volume ratio of nitrogen and oxygen (mixed gas) is 9:1, the sintering temperature is 550° C., and the sintering time is 3 h, to obtain the rod-shaped manganese oxide with Mn:O=1;2.1 and a C content of 7%.
[0025] Example 3 The preparation method of the active manganese sheet comprises the following steps: (1) Ultrafine PET staple fibers and PET long fibers are opened in an opening machine respectively; (2) Spreading the opened PET long fibers evenly on a polytetrafluoroethylene conveyor belt to form a PET long fiber layer; (3) spraying a layer of manganese oxide mixed glue on the PET long fiber layer 1 to form a mixed glue layer 1, then evenly spreading a layer of ultrafine PET short fiber on the mixed glue layer 1 to form a PET short fiber layer, then spraying a layer of manganese oxide mixed glue on the PET short fiber layer to form a mixed glue layer 2, and finally evenly spreading a layer of PET long fiber on the mixed glue layer 2 to form a long fiber layer 2, to obtain a composite material; (4) The composite material is sequentially pre-dried in a microwave drying oven, passed through a hot press roller, and passed through a hot air dryer to obtain a dried composite material; wherein the pre-drying power is 400W / m 2 , pre-baking time 3min; overheating roller temperature 150℃, increase the compactness of the composite material and increase the distribution uniformity of manganese oxide; (5) The dried composite material is shaped by a second hot pressing roller at a temperature of 150°C.
[0026] The prepared active manganese sheet has a gram weight of 110g / m 2 The weight of the long fiber layer 1 and the long fiber layer 2 are 35g / m 2 , staple fiber layer weight 10g / m 2 The weight of mixed adhesive layer 1 and mixed adhesive layer 2 are 20g / m 2 .
[0027] The manganese oxide mixed glue is mixed with the following raw materials in mass fractions: Rod-shaped manganese oxide: 20%, Heavy calcium powder: 20%, Modified acrylic emulsion: 20%, Water: 39.6%, Dispersant: 0.3%, Wetting agent: 0.1%.
[0028] The rod-shaped manganese oxide is the rod-shaped manganese oxide prepared in Example 1; The ultrafine PET short fiber has a fineness of 0.4dtex and a length of 3mm; the PET long fiber has a fineness of 2.3dtex and a length of 38mm.
[0029] Example 4 The only difference between Example 4 and Example 3 is that the rod-shaped manganese oxide used is the rod-shaped manganese oxide prepared in Example 2.
[0030] Comparative Example 1 Commercially available mineral manganese dioxide powder, purity ≥80%, Hunan Qingchong New Materials Co., Ltd.
[0031] An active manganese sheet was prepared by replacing the rod-shaped manganese oxide in Example 3 with the manganese dioxide powder of Comparative Example 1 in equal amounts.
[0032] Comparative Example 2 References: Qian Dong, Lv Linlin, Wang Hongen, "Hydrothermal Synthesis and Electrochemical Performance of Manganese Dioxide Nanorods", Mining and Metallurgical Engineering, October 2009, Vol. 29, No. 5, 61-64. The preparation method of manganese dioxide nanorods is as follows: 2mmol KMnO4 and 1mL of 98% concentrated sulfuric acid are added to a 36mL container, and the reaction is carried out at a constant temperature of 150℃ for 12h, centrifuged and washed, and dried at 110℃ for 6h to obtain the obtained nanorods.
[0033] The manganese dioxide nanorods of Comparative Example 2 were used to replace the rod-shaped manganese oxide in Example 3 in equal amounts to prepare active manganese sheets.
[0034] Comparative Example 3 The manganese dioxide nanorods prepared in Comparative Example 2 were prepared into a 5% (mass percentage) dispersion, mixed with a 3% (mass percentage) graphene oxide dispersion at a mass ratio of 5.4:1 at room temperature, aged for 24 hours, and dried at 80°C to obtain graphene-loaded manganese dioxide nanorods of Comparative Example 3.
[0035] The graphene-supported manganese dioxide nanorods of Comparative Example 3 were used to replace the rod-shaped manganese oxide in Example 3 in equal amounts to prepare active manganese sheets.
[0036] Comparative Example 4 The difference between Comparative Example 4 and Comparative Example 3 is that the formula of the mixed glue is as follows: Graphene loaded manganese dioxide nanorods: 30%, Heavy calcium powder: 10%, Modified acrylic emulsion: 20%, Water: 39.6%, Dispersant: 0.3%, Wetting agent: 0.1%.
[0037] The prepared active manganese sheet has a gram weight of 110g / m 2 The weight of the long fiber layer 1 and the long fiber layer 2 are 35g / m 2 , staple fiber layer weight 10g / m 2 The weight of mixed adhesive layer 1 and mixed adhesive layer 2 are 20g / m 2 .
[0038] Comparative Example 5 The difference between Comparative Example 4 and Comparative Example 3 is that the formula of the mixed glue is as follows: Graphene-loaded manganese dioxide nanorods: 40%, Modified acrylic emulsion: 20%, Water: 39.6%, Dispersant: 0.3%, Wetting agent: 0.1%.
[0039] The prepared active manganese sheet has a gram weight of 110g / m 2 The weight of the long fiber layer 1 and the long fiber layer 2 are 35g / m 2 , staple fiber layer weight 10g / m 2 The weight of mixed adhesive layer 1 and mixed adhesive layer 2 are 20g / m 2 .
[0040] Performance Testing Mixed adhesive layer 1 and mixed adhesive layer 2 The active manganese sheets obtained in Examples 3-4 and Comparative Examples 1-3 were tested according to QB / T2761-2006 "Method for Determining the Purification Effect of Indoor Air Purification Products", and the results are shown in Table 1.
[0041] Table 1 Performance test table of Examples 3-4 and Comparative Examples 1-5
[0042] As can be seen from Table 1, the doping of rare earth elements in the present invention is conducive to improving the formaldehyde decomposition rate; the mineral manganese dioxide powder in Comparative Example 1 has more impurities and a more complex crystal form; the manganese dioxide of the present invention is loaded on the surface of graphene oxide, which can increase the active sites of the catalytic oxidation reaction and improve the formaldehyde decomposition rate of manganese dioxide to a certain extent. From the two groups of data in Comparative Examples 2 and 3, it can be found that the use of graphene loaded manganese dioxide nanorods can improve its efficiency in catalytic decomposition of formaldehyde, but the degree of improvement is still significantly lower than that of the present invention.
[0043] The mass of the manganese dioxide nanorods used in Comparative Example 4 is 1.5 times that of Examples 1 and 2, and the mass of the manganese dioxide nanorods used in Comparative Example 5 is 2 times that of Examples 1 and 2, but their formaldehyde decomposition rates are both lower than those of the examples, indicating that the manganese dioxide nanorods prepared according to the method of the present invention can play a better role with less dosage.
[0044] The manganese oxide obtained in Example 1 was characterized by SEM. Figure 1 , it can be seen that rod-shaped doped manganese dioxide grows evenly on the surface of graphene oxide, with a diameter of about 300nm and a length of about 2μm.
Claims
1. A method for preparing rod-shaped manganese oxide for removing formaldehyde, characterized in that: The steps include: (1) reacting concentrated sulfuric acid, flake graphite and potassium permanganate at 30-85° C. for 1-48 hours to obtain a mixture 1; (2) adding neutralizer 1 and neutralizer 2 to mixture 1 in sequence, adjusting the pH value to 5-9, and obtaining mixture 2; (3) After the mixture is aged for a second time, the precipitate is washed to a pH value of 6-8 in a 1 wt.% aqueous dispersion, and then dried to obtain a dried product; (4) The dried product is placed in a tubular furnace and sintered in a nitrogen and oxygen mixed atmosphere to obtain the product.
2. The method for preparing rod-shaped manganese oxide for removing formaldehyde according to claim 1, characterized in that: In step (1), based on the total mass of concentrated sulfuric acid, flake graphite and potassium permanganate as 100%, the mass fractions of concentrated sulfuric acid, flake graphite and potassium permanganate are 40%-90%, 1%-30% and 1%-30% respectively.
3. The method for preparing rod-shaped manganese oxide for removing formaldehyde according to claim 1, characterized in that: The diameter of flake graphite is 40-5000 mesh.
4. The method for preparing rod-shaped manganese oxide for removing formaldehyde according to claim 1, characterized in that: In step (2), the neutralizer 1 is one or more oxides or hydroxides of rare earth elements; the neutralizer 2 is one or more hydroxides of alkali metal elements and oxides or hydroxides of alkaline earth metals; and the mass ratio of the neutralizer 1 to the neutralizer 2 is 1:(0.1-10).
5. The method for preparing rod-shaped manganese oxide for removing formaldehyde according to claim 1, characterized in that: In step (3), the aging time is 1-48 hours and the drying temperature is 80-200°C.
6. The method for preparing rod-shaped manganese oxide for removing formaldehyde according to claim 1, characterized in that: In step (4), the volume ratio of nitrogen to oxygen is (1-10):1, the sintering temperature is 300-800°C, and the sintering time is 0.5-6h.
7. A rod-shaped manganese oxide for removing formaldehyde, characterized in that: The method is prepared by the preparation method described in claims 1 to 6.
8. An active manganese sheet for removing formaldehyde prepared by using the rod-shaped manganese oxide according to claim 7, characterized in that: From bottom to top, it is composed of PET long fiber layer 1, mixed rubber layer 1, PET short fiber layer, mixed rubber layer 2, and PET long fiber layer 2. The PET long fiber layer 1 and the PET long fiber layer 2 are composed of PET long fibers, the PET short fiber layer is composed of ultra-fine PET short fibers, the mixed rubber layer 1 and the mixed rubber layer 2 are composed of manganese oxide mixed rubber, and the manganese oxide mixed rubber is mixed by the following raw materials in mass fractions: Rod-shaped manganese oxide: 10%-20%, Heavy calcium powder: 10-20%, Modified acrylic emulsion: 10%-20%, Dispersant: 0.3%, Wetting agent: 0.1%, The balance is water.
9. The active manganese sheet for removing formaldehyde according to claim 8, characterized in that: The fineness of ultrafine PET staple fiber is ≤0.4dtex and the length is ≤3mm; the fineness of PET long fiber is 1.7-2.3dtex and the length of PET long fiber is ≥38mm.
10. A method for preparing the active manganese sheet according to any one of claims 8 and 9, characterized in that: The steps include: (1) Ultrafine PET staple fibers and PET long fibers are opened in an opening machine respectively; (2) Spreading the opened PET long fibers on a plane to form a PET long fiber layer; (3) spraying a layer of manganese oxide mixed glue on the PET long fiber layer 1 to form a mixed glue layer 1, then spreading a layer of ultrafine PET short fiber on the mixed glue layer 1 to form a PET short fiber layer, then spraying a layer of manganese oxide mixed glue on the PET short fiber layer to form a mixed glue layer 2, and finally evenly spreading a layer of PET long fiber on the mixed glue layer 2 to form a long fiber layer 2, to obtain a composite material; (4) Pre-drying the composite material in a microwave oven, passing through a hot roller, and passing through a hot air dryer to obtain a dried composite material; wherein the pre-drying power is 200-500W / m 2 , pre-baking time 1-3min; overheating roller temperature 120-160℃; (5) The dried composite material is shaped by a second hot pressing roller at a temperature of 140-160°C.